ANALISIS KELAYAKAN FINANSIAL AGROFORESTRI SUREN (Toona sureni Merr.) DAN KOPI ARABIKA (Coffea arabica L.) - Hana C. Situmeang; Siti Latifah; Alfonsus H. Harianja (Program studi Kehutanan USU, 2016)
The research is purposed to assess the financial feasibility of agroforestry system which consisted of “suren” (Toona sureni Merr.) and arabica coffee (Coffea arabica L.) in Aek Nauli and Sipolha Horizon Village, North Sumatra. The data was collected from farmers in both villages from March up to July 2015, then analysed using financial feasibility parameters such as NPV, BCR, and IRR. The results shows that this farming system is financially feasible at the interest rates of 5,65% for the average farming scale amounted to 0,22 hectares per 15 years cycle. This system emerges NPV value IDR. 166.792.215,73/cycle/farm, BCR value is 22,80, and IRR is 38,90%. Based on these findings it is needed to compensate additional input for the farmers who can’t harvest their suren which is located on the buffer zone because the stands are utilized to conserve the vulnerable site. Keywords: financial feasibility, agroforestry, intercropping, arabica coffee, suren (Toona sureni)